2023
DOI: 10.1186/s13054-022-04294-5
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and outcomes of early-onset AKI in COVID-19-related ARDS in comparison with non-COVID-19-related ARDS: insights from two prospective global cohort studies

Abstract: Background Acute kidney injury (AKI) is a frequent and severe complication of both COVID-19-related acute respiratory distress syndrome (ARDS) and non-COVID-19-related ARDS. The COVID-19 Critical Care Consortium (CCCC) has generated a global data set on the demographics, management and outcomes of critically ill COVID-19 patients. The LUNG-SAFE study was an international prospective cohort study of patients with severe respiratory failure, including ARDS, which pre-dated the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…In our analysis, the PARI cutoff point of ≥ 4 was the one that best discriminated persistent AKI in patients admitted to the ICU for acute respiratory failure, lower than the ≥ 8 identified by Matsuura et al ( 7 ) The lower PARI score found in our study could mean that the population with acute respiratory failure is more likely to develop renal dysfunction in the first 7 days after ICU admission, reinforcing the lung-kidney crosstalk, ( 23 - 25 ) and/or it could mean our population was not as severe at ICU admission, given their SOFA and APACHE II values.…”
Section: Discussioncontrasting
confidence: 42%
“…In our analysis, the PARI cutoff point of ≥ 4 was the one that best discriminated persistent AKI in patients admitted to the ICU for acute respiratory failure, lower than the ≥ 8 identified by Matsuura et al ( 7 ) The lower PARI score found in our study could mean that the population with acute respiratory failure is more likely to develop renal dysfunction in the first 7 days after ICU admission, reinforcing the lung-kidney crosstalk, ( 23 - 25 ) and/or it could mean our population was not as severe at ICU admission, given their SOFA and APACHE II values.…”
Section: Discussioncontrasting
confidence: 42%
“…Moreover, AKI in the setting of COVID-19 tends to be more severe. As compared to historical controls, COVID-19 patients had a 2.6-fold higher mortality and an increased requirement for RRT [ 37 , 38 ]. A recent meta-analysis involving over 25,000 COVID-19 patients found a pooled incidence of AKI of 53% in those with severe disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the current narrative review, we have carried out a pooled analysis of the medical literature regarding the incidence of AKI in hospitalized patients with COVID-19. We have included 24 reports ( n = 502, 593 unique patients) and found an incidence of AKI of 31.8% (range, 0.5% to 56.9%) ( Table 1 ) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Many surveys ( n = 9) were published very recently (2022–2023) ( Table 1 ).…”
Section: Sars-cov-2 and Kidneys: Epidemiology Of Aki (Pooled Analysis)mentioning
confidence: 99%
“…As listed in Supplementary Table S1 , most reports had a retrospective design, and a few ( n = 2) had a prospective nature [ 35 , 49 ]. Some ( n = 7) had a multicenter approach [ 31 , 38 , 40 , 42 , 45 , 46 , 50 ]. The weighted average of male frequency was 52% (range, 37.1% to 74.6%).…”
Section: Sars-cov-2 and Kidneys: Epidemiology Of Aki (Pooled Analysis)mentioning
confidence: 99%